HUBUNGAN STATUS GIZI DENGAN PERKEMBANGAN ANAK USIA 1 – 5 TAHUN DI POSYANDU DESA SIRNOBOYO KABUPATEN WONOGIRI - Ratna Indriati; Yurika Kristi Murpambudi (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2016)
Background Child under five years of age is the period of life that are veryimportant and need serious attention. During this process of growth anddevelopment very rapidly. One of the important factors that affect childdevelopment is a nutritional factorThe purpose of this study was to determine the relationship of nutrition statuswith the development of children aged 1-5 years in Sirnoboyo village of PosyanduWonogiri RegencyMethod Correlation research design with cross sectional approach . The subjectof research is the 35 children aged 1-5 years with his mother in Sirnoboyo villageof posyandu Wonogiri Regency with technique purposive sampling. Dataobtained by doing observation to know nutritional status and child development.The data obtained are then analyzed by chi square test with p = 0.05Results showed the child with good nutritional status of as many as 25 children(71,43%), nutritional status less as much as 9 child (25.71%) and betternutritional status as much as 1 child (2.86%) while the children with normaldevelopment of as many as 24 children (68,57%) and a total of 11 children ofquestionable developments (31,43%). The results of the analysis using the chisquaretest p = 0.006 obtained so that the value of p < 0.05, which means that Hois rejected and Ha accepted.The Conclusion of the research was there is relationship of the nutritional statuswith the development of children aged 1-5 years in Sirnoboyo village of posyanduWonogiri RegencyKeywords : Nutritional Status, Development